Competition between hybrid suffixed denominal personal nounsand common root borrowings in contemporary Lithuanian - Stundžia, Bonifacas; Inčiuraitė-Noreikienė, Lina (Baltistica, 2022)
The article analyzes how hybrid suffixed denominal personal derivatives compete with each other (e.g. atlant-inink-as, -ė / atlant-iet-is, -ė ‘supporter of NATO’ ← Atlant-as ‘Atlantic’) and with suffixed borrowings or correlative common root derivatives of the same derivational category (e.g. strateg-inink-as, -ė ‘strategist’ ← strategij-a / strateg-ist-as, -ė ‘id.’ ⇠ strategij-a ‘strategy’) and common root simplex borrowings (e.g. strateg-inink-as, -ė / strateg-as, -ė ‘strategist’) in the contemporary Lithuanian language. The aim is to identify the competing patterns of suffixed denominal personal nouns with borrowed roots, to find out how diverse competing hybrid and correlative derivatives are from the perspective of derivation and how frequent they are in the contemporary Lithuanian language. We distinguish between strong and weak competition according to the frequency of use of derivatives. The material for the study was collected from the electronic Dictionary of Internationalisms “Interleksis”, Dictionary of Contemporary Lithuanian, Dictionary of Standard Lithuanian, Dictionary of Lithuanian, the Database of Lithuanian Neologisms, the Corpus of the Contemporary Lithuanian Language and internet sources.